The impact of weight bias in forensic medicine: Challenges and implications for objectivity in medical legal practice - Amelia RIZZO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2024)
Weight bias, defined as negative attitudes and stereotypes directed toward individuals based on their weight, has profound implications in healthcare and legal settings. In forensic medicine, where objective assessments are critical to the pursuit of justice, weight bias can distort clinical and legal evaluations. This article examines the prevalence of weight bias in forensic medicine, its impact on disability judgments and medical-legal outcomes, and proposes solutions for mitigating bias to ensure fairness and accuracy. Emphasizing the need for education and standardized guidelines, we argue that addressing weight bias is essential for maintaining the integrity of forensic science and bio-psycho-social evaluation.